A new doubly resolvable candelabra quadruple systems - Zhaoping Meng; Qingling Gao (Examples and Counterexamples, 2023)
Two resolutions of the same design are said to be orthogonal when each parallel class of one resolution has at most one block in common with each parallel class of the other resolution. If a candelabra quadruple system has two mutually orthogonal resolutions, the design is called doubly resolvable candelabra quadruple system and denoted by DRCQS. In this paper, we obtain a DRCQS(35:1)by computer search.